3D Hetero-architecture of GdB6 nanoparticles on lessened cubic Cu2O nanowires: enhanced field emission behaviour1. Issue 21 (7th June 2015) - Suryawanshi, Sachin R.; Singh, Anil K.; Deo, Meenal; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A.
<x xml:space="preserve">Abstract</x> The simplicity of the synthesis route coupled with better field emission properties of the GdB6/Cu2O hetero-architecture makes it a promising cathode for high current density applications.